ASSESSMENT OF THE IMPACT OF TRAINING AND DEVELOPMENT PROGRAMMES ON ACADEMIC STAFF PERFORMANCE IN GOMBE STATE UNIVERSITY - Bappi, Usman; Bello, Muhammad; Jamari, Abubakar Abdulkadir (African Journal of Social and Behavioural Sciences, 2024)
The study aims to assess the impact of training and development programmes on academic staff performance in Gombe State University. The descriptive survey design method was adopted for research design. Using a proportionate sampling and simple random sampling as a sampling technique, 238 respondents were selected using the Slovene’s formula, out of the target population of 596 academic staff of Gombe State University. A self-administered Questionnaire was used as a source of primary data, and the data collected were analysed using descriptive statistics and Pearson’s correlation analysis with the aid of IBM SPSS Statistic Version 21. The major findings revealed that there was positive significant correlation between academic study fellowship (ASF) and staff performance (SP), Academic Conference Attendance (ACA) and staff performance (SP) and Academic Workshop Attendance (AWA) and staff performance (SP). The study recommended that the university management should create additional means of sponsoring academic staff for training and development programmes. This can help in reducing long queues waiting for academic staff to benefit from the training and development programme of the university. The study also recommended that the university management should publish policy document guideline on training and development programmes of the university and ensure the availability of such document to academic staff of the university.